Aplikasi Monitoring Volume Cairan Infus pada Pasien - Hasanah, Afifah Nur; Cahyadi, Irsan; Irwan, Irwan; Saputra, Zanu (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Infusion or intravenous fluids are given through a vein to replace fluids or nutrients lost from the body. Manual monitoring of infusions by nurses often carries a risk of error. To overcome this, a tool was developed that uses a loadcell sensor to measure liquid weight, an infrared sensor to detect droplets, and an ESP32 module to send data in real time to a database and display it on a monitor screen or website. This system provides a warning when the infusion fluid is less than 100 ml. Even so, there is an error in the loadcell sensor of 0.1% -0.2%, and the drip sensor readings are sometimes not detected due to certain factors. Apart from monitoring infusion fluids, the system also allows input of patient data via the website. Overall, the tool functions as intended, although there are still some aspects that need improvement.